Urban landscapes and textual spaces: three portrayals of Glasgow by A.L. Kennedy, Janice Galloway and Jackie Ka (Philologia, 2021)
The aim of this paper is to analyse recent changes in the literary representation of the city of Glasgow. This text revises the most significant approaches to the space in Scottish culture in the twentieth century, from its highly masculinised working-class associations to more contemporary perspectives that negotiate ethnic and gender difference: The Scottish Renaissance of the inter-war period, the “Glasgow Group” of the late 1970s, and finally a younger generation of writers who began their careers in the late 1980s. In order to explore new literary cartographies of the city, this article focuses on the works of three of Scotland’s most recognised writers, A. L. Kennedy, Janice Galloway and Jackie Kay. Firstly, from a Foucauldian perspective, it considers Kennedy’s “The Role of Notable Silences in Scottish History” and its portrayal of Glasgow as a textual space. Secondly, it studies gendered analysis of the city, such as Linda McDowell’s, to interpret Janice Galloway’s The Trick is to Keep Breathing and its incorporation of female subjectivity in the segregation of the urban. Finally, this paper considers the works of Jackie Kay and their negotiation of ethnic and sexual difference in the context.